EVALUATION OF IN VITRO ANTIDIABETIC ACTIVITY OF METHANOLIC EXTRACT OF SEAGRASS HALOPHILA BECCARII - M, Vani; T, Vasavi; Devi P, Uma Maheswari (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The objectives of this study were to analyze the in vitro antidiabetic activity of methanolic extract of seagrass. Methods: The methanolic extract of Halophila beccarii was tested for its in vitro antidiabetic potential through inhibition of carbohydrate digestive enzymes such as Î±- amylase and Î±-glucosidase, glucose diffusion assay, glucose adsorption capacity, and enhancement of glucose uptake activity in yeast cells. Results: The crude extract of H. beccarii showed strong inhibition of É‘-amylase and É‘-glucosidase as on comparison with the standard enzyme inhibitor acarbose. The antidiabetic activity was found to be concentration dependent, and the antihyperglycemic activity was demonstrated through the inhibition of the glucose movement and facilitated diffusion of glucose. The rate of glucose diffusion across the membrane was found to be increased from 30 to 180 min. Conclusion: The seagrass collected from Pulicat Lake was identified as H. beccarii based on the morphology of the plant, shape of the leaves, and brown pigmentation on the leaves. According to the results, H. beccarii showed antidiabetic activity by the inhibition of carbohydrate digestive enzymes and glucose movement; hence, it is significantly reduced the post-postprandial hyperglycemia.